Catalytic Enantioselective Synthesis of Tertiary Thiols From 5H‐Thiazol‐4‐ones and Nitroolefins: Bifunctional Ureidopeptide‐Based Brønsted Base Catalysis1. Issue 45 (17th September 2013) - Diosdado, Saioa; Etxabe, Julen; Izquierdo, Joseba; Landa, Aitor; Mielgo, Antonia; Olaizola, Iurre; López, Rosa; Palomo, Claudio
<x xml:space="preserve">Abstract</x> Fully loaded: The ureidopeptide‐based bifunctional Brønsted base 1 efficiently promotes the first direct catalytic Michael reaction of α‐mercapto carboxylate surrogates with nitroolefins involving a fully substituted α‐carbon atom construction.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>